What's new in Adobe Flash Professional CS5.5 and ActionScript 3.0 learn by video - McCarthran, Kelly (Peachpit Press, 2011)
"This innovative product is a focused video workshop ... that will teach Flash developers how to get up to speed on the new features of Adobe Flash CS5.5 and ActionScript 3.0. Take advantage of new features including improvements to Flash's powerful TLF type engine, improved layout fidelity, and enhancements to the already powerful inverse kinematics bone tool, as well as updates to ActionScript. Tips and tricks for all versions of Flash are sprinkled throughout. Experienced instructor Kelly McCathran presents three hours of exceptional quality video tutorials, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside in Flash and ActionScript. Project files used in the lessons are included on the disc so viewers can practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.
Title from resource description page (viewed Aug. 11, 2011)
Keywords: Flash (Computer file); ActionScript (Computer program language); Smartphones -- Programming; Computer animation; Mobile computing -- Programming; ActionScript (Langage de programmation); Téléphones intelligents; Programmation; Animation par ordinateur; Informatique mobile; Programmation; computer animation